1996
DOI: 10.1007/bf00127305
|View full text |Cite
|
Sign up to set email alerts
|

A method for checking regression models in survival analysis based on the risk score

Abstract: We propose to perform model check for the Cox and Aalen regression models using martingale residual processes grouped after the risk score. Asymptotic distributions of the grouped martingale residual processes are deduced, so both formal and graphical model check can be performed. The method is validated by stochastic simulation. A data example with patients with primary biliary cirrhosis of the liver is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
145
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(148 citation statements)
references
References 14 publications
0
145
0
1
Order By: Relevance
“…19 Calibration is the agreement between the predicted risks and the observed risks of MACE and was tested with the calibration plot and Gronnesby and Borgan test. 22 For presentation and application of our model, we developed a score chart using previously described methods 23 and subsequently divided patients into 4 risk groups. Although cutoff points for primary cardiovascular risk estimation have been described in population-based studies, 24,25 no cutoff points are available for risk estimation of secondary cardiovascular events.…”
Section: Model Validation and Presentationmentioning
confidence: 99%
“…19 Calibration is the agreement between the predicted risks and the observed risks of MACE and was tested with the calibration plot and Gronnesby and Borgan test. 22 For presentation and application of our model, we developed a score chart using previously described methods 23 and subsequently divided patients into 4 risk groups. Although cutoff points for primary cardiovascular risk estimation have been described in population-based studies, 24,25 no cutoff points are available for risk estimation of secondary cardiovascular events.…”
Section: Model Validation and Presentationmentioning
confidence: 99%
“…One can perform more formal tests to assess normality (e.g., KolmogorovSmirnov, Cramér-von Mises, Anderson-Darling). Grønnesby and Borgan (1996) concluded that when β is one-dimensional, (3.7) only checks the coding of the covariate. However, when β is of higher dimension, W(z) cannot detect whether the effects of covariates vanish with time or not.…”
Section: Diagnostics Based On Martingale Residualsmentioning
confidence: 99%
“…However, when β is of higher dimension, W(z) cannot detect whether the effects of covariates vanish with time or not. Grønnesby and Borgan (1996) grouped the individuals after their linear predictions, i.e., replaced I(β…”
Section: Diagnostics Based On Martingale Residualsmentioning
confidence: 99%
“…28 Discrimination was assessed by Harrell c-statistic and the optimism-corrected c-statistic was obtained by 1000-fold bootstrap resampling.…”
Section: Assessment Of Model Performancementioning
confidence: 99%